PENCEGAHAN BULLYING PADA ANAK MELALUI PENYULUHAN ANTI BULLYING DI PANTI ASUHAN TAQWA AL QOLBI - Zanah, Inggrit Mifrahul; Putri , Kalina Dewantara; Sriwulandari , Yunita Anas; Lutfiyah, Luly Zahrotul; Sorraya , Artifa (Inspirasi: Jurnal Pengabdian Masyarakat, 2025)
Potential-Based Community Service (PMBP) is a community service program. The implementation of the PMBP program is carried out in a balanced manner starting with planning, implementation and evaluation at the end of each program. The results achieved from the entire PMBP program include improving the welfare of orphaned children through providing education (literacy and numeracy). Literacy and numeracy help a person gain the basic skills needed to achieve success in life. Literacy programs are also implemented to develop quality human resources from an early age. In the environmental sector, maintaining health by providing education and simple practices on how to wash hands properly and correctly at the orphanage received a response and participation from the children of the Taqwa Al – Qolbi orphanage. However, we focus more on anti-bullying education which is useful for preventing children from committing acts of bullying from a young age. This is more focused on because bullying behavior is very dangerous for everyone’s mental health. So with this bullying education, we hope that children will understand the dangers of bullying.